HYPNOSIS MODEL TOWARDS UNIVERSITY STUDENTS’ THINKING SKILL - Prana Jaya, Yohanes Michell Darius; Sidqi, M. Fajru (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
Nowadays, learning activity in University expects student to build the mind set in cognitive structure and improving the thinking skill of student. Every movement in our ideas, concepts, and so forth is called as thinking. However, the way how to build this skill is still less. This paper is design using library research model which analyse the data qualitatively. Moreover, this also telling about how the lecturer can fulfil and improving the students’ thinking skill with a hypnosis model. Changing perception that learning is not about the score but how we can develop our mind to be creative. APA Division 30 state that hypnosis is a state of consciousness involving focused attention and reduced peripheral awareness characterized by an enhanced capacity for response to suggestion. Therefore, using hypnosis model can train university students’ mind to think out of the box and not fixated with the material. Through the subconscious mind of student, the lecturer gives the point or clue of the material and they will develop by their own.